COMPARATIVE ANALYSIS OF BIOCHEMICAL MARKERS OF HYPOTHYROIDISM IN WOMEN AFTER TOTAL AND SUBTOTAL STRUMECTOMY - Madvalieva Hushnoza Mansurjonovna (Modern American Journals, 2025)
This study aims to compare the biochemical markers of primary hypothyroidism in women after total and subtotal strumectomy. A total of 72 patients were included. Levels of thyroid-stimulating hormone (TSH), free thyroxine (T4), anti-thyroid peroxidase antibodies (anti-TPO), and lipid profiles were analyzed. Findings revealed more pronounced hormonal and metabolic alterations in women who underwent total strumectomy. These results emphasize the need for thorough monitoring and personalized hormone replacement therapy.
Keywords: Hypothyroidism, TSH, thyroxine, anti-TPO, strumectomy, biochemical markers